Longitudinal bio‐logging reveals interplay between extrinsic and intrinsic carry‐over effects in a long‐lived vertebrate. Issue 8 (1st August 2014) - Daunt, F.; Reed, T. E.; Newell, M.; Burthe, S.; Phillips, R. A.; Lewis, S.; Wanless, S.
Abstract : Carry‐over effects have major implications for individual fitness and population and evolutionary dynamics. The strength of these effects is dependent on an individual's intrinsic performance and the environmental conditions it experiences. However, understanding the relative importance of environmental and intrinsic effects underpinning seasonal interactions has proved extremely challenging, since they covary. A powerful approach is longitudinal measurement of individuals across a range of conditions, whereby each animal is effectively acting as its own control. We related time spent foraging during the nonbreeding period to subsequent breeding performance in European Shags Phalacrocorax aristotelis . By following individuals for up to six years, we could test simultaneously for extrinsic and intrinsic effects using random regression modeling. We detected significant annual and among‐individual variation in daily foraging time during the late winter, and clear variation among individuals in the quadratic relationship between foraging time and date. Shorter foraging times were associated with earlier and more successful breeding, driven by differences among years and individuals, with no evidence of individual variation in the slope of these relationships. That both environmental and intrinsic variation shape carry‐over effects has important implications for population responses to environmental change.